Kitchen Poverty. The Anthropological Sketch about Food and Space - Kuźma, Inga B. (In the Kitchen. Cultural Sketches on Space, 2019)
The article applies to cooking and eating, which also belong to the scope of social assistance, provided to people experiencing homelessness or at risk of homelessness. Food and kitchen facilities are marked by the status of their users and recipients. People who can almost exclusively rely on outside help eat either what they can get from others (by begging, by searching the rubbish bins) or what they receive from others (all forms of official and voluntary food supply). Products that are used to prepare meals, as well as the manner and place of their preparation, consumption or issuance, are marked by people who use this form of help. The more so because this kind of feeding is subject to many restrictions included, among others in laws, regulations and other state guidelines and in internal institutional regulations. In this context, the kitchen appears primarily as a practice securing the biological possibility of survival and satisfying hunger. However, you can also find examples when eating practices provide emotional and social support. The symbol of solidarity may be a meal offered by Food not Bombs or a kitchen – a common place, where “sharing yourself ”, sharing emotions, and not just eating. The author shows the diversity of attitudes towards the kitchen, food and as nutrition, drawing examples from her own field research, conducted in 2009 in Lodz institutions specializing in helping people experiencing homelessness or being at risk.